Entre chegadas e partidas: a sociabilidade em trânsito - Lemos, Marcelo Rodrigues (2012)
New ways of sociability can be perceive in a historical context marked by the social change. The investigation developed by this thesis follow this idea, pointing the emergency of social relations established between individuals in drift. The foremost aim of this research was to assay, using a case study, the bonds constructed among the people that attend the Terminal Central - Pratic Shopping of Uberlândia-MG, the main responsible for the reception and distribution of public transport of the city. With the growth of the urban centers, their population became attractive objects of analysis in the social science field and the understanding of the city, in their core, by the dwellers displacement. Thus, after the separation of the people that use the Terminal Central in seven groups (students, families and couples, elderly, deaf and/or mute, employees of the stores in Terminal and of the bus companies), their interactions tried to be understood, by identifying the similarity with the sociability in traffic studies. In places with a great flow of people, the sociability in traffic suggests bonds of friendship, kindness, as foray, impersonality, frailty and the sudden break of contact.